Promoting Immortalized Adipose-Derived Stem Cell Transdifferentiation and Proliferation into Neuronal-Like Cells through Consecutive 525 nm and 825 nm Photobiomodulation - Madeleen Jansen van Rensburg; Anine Crous; Heidi Abrahamse (Stem Cells International)
Neuronal cells can be generated from adipose-derived stem cells (ADSCs) through biological or chemical inducers. Research has shown that this process may be optimized by the introduction of laser irradiation in the form of photobiomodulation (PBM) to cells. This in vitro study is aimed at generating neuronal-like cells with inducers, chemical or biological, and at furthermore treating these transdifferentiating cells with consecutive PBM of a 525 nm green (G) laser and 825 nm near-infrared (NIR) laser light with a fluence of 10 J/cm2. Cells were exposed to induction type 1 (IT1): 3-isobutyl-1-methylxanthine (IBMX) (0.5 mM)+indomethacin (200 μM)+insulin (5 μg/ml) for 14 days, preinduced with β-mercaptoethanol (BME) (1 mM) for two days, and then incubated with IT2: β-hydroxyanisole (BHA) (100 μM)+retinoic acid (RA) (10-6 M)+epidermal growth factor (EGF) (10 ng/ml)+basic fibroblast growth factor (bFGF) (10 ng/ml) for 14 days and preinduced with β-mercaptoethanol (BME) (1 mM) for two days and then incubated with indomethacin (200 μM)+RA (1 μM)+forskolin (10 μM) for 14 days. The results were evaluated through morphological observations, viability, proliferation, and migration studies, 24 h, 48 h, and 7 days post-PBM. The protein detection of an early neuronal marker, neuron-specific enolase (NSE), and late, ciliary neurotrophic factor (CNTF), was determined with enzyme-linked immunosorbent assays (ELISAs). The genetic expression was also explored through real-time PCR. Results indicated differentiation in all experimental groups; however, cells that were preinduced showed higher proliferation and a higher differentiation rate than the group that was not preinduced. Within the preinduced groups, results indicated that cells treated with IT2 and consecutive PBM upregulated differentiation the most morphologically and physiologically.